Inhibition of Soluble Epoxide Hydrolase Attenuates Bosutinib-Induced Blood Pressure Elevation. Issue 5 (4th October 2021) - Cui, Zhen; Li, Bochuan; Zhang, Yanhong; He, Jinlong; Shi, Xuelian; Wang, Hui; Zhao, Yinjiao; Yao, Liu; Ai, Ding; Zhang, Xu; Zhu, Yi
Abstract : Supplemental Digital Content is available in the text. Abstract : Endothelial cells play a critical role in maintaining homeostasis of vascular function, and endothelial activation is involved in the initial step of atherogenesis. Previously, we reported that Abl kinase mediates shear stress–induced endothelial activation. Bosutinib, a dual inhibitor of Src and Abl kinases, exerts an atheroprotective effect; however, recent studies have demonstrated an increase in the incidence of side effects associated with bosutinib, including increased arterial blood pressure (BP). To understand the effects of bosutinib on BP regulation and the mechanistic basis for novel treatment strategies against vascular dysfunction, we generated a line of mice conditionally lacking c-Abl in endothelial cells (endothelial cell- Abl KO ). Knockout mice and their wild-type littermates ( Abl f/f ) were orally administered a clinical dose of bosutinib, and their BP was monitored. Bosutinib treatment increased BP in both endothelial cell- Abl KO and Abl f/f mice. Furthermore, acetylcholine-evoked endothelium-dependent relaxation of the mesenteric arteries was impaired by bosutinib treatment. RNA sequencing of mesenteric arteries revealed that the CYP (cytochrome P450)-dependent metabolic pathway was involved in regulating BP after bosutinib treatment. Additionally, bosutinib treatment led to an upregulation of soluble epoxide hydrolase in the arteries and a lower plasma content of eicosanoid metabolites in the CYP pathway in mice. Treatment with 1-Trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea, a soluble epoxide hydrolase inhibitor, reversed the bosutinib-induced changes to the eicosanoid metabolite profile, endothelium-dependent vasorelaxation, and BP. Thus, the present study demonstrates that upregulation of soluble epoxide hydrolase mediates bosutinib-induced elevation of BP, independent of c-Abl. The addition of soluble epoxide hydrolase inhibitor in patients treated with bosutinib may aid in preventing vascular side effects.